Rainfall Runoff Modeling Using HEC-HMS: The Case of Awash Bello Sub-Catchment, Upper Awash Basin, Ethiopia - Geyisa Namara, Wana; Adugna Damise, Tamane; Gudu Tufa, Fayera (International Journal of Environment, 2020)
Rainfall runoff modeling is one of the most complex hydrological modeling due to the involvement of different watershed physical parameters. It is essential for the analysis of watershed hydrological response toward the received precipitation under the influence of watershed parameters. As it is a replica of watershed hydrological response, rainfall runoff modeling is essential to evaluate the general characteristics of total surface runoff at catchment’s outlet. The main objective of this study was rainfall runoff modeling using HEC-HMS for Awash Bello sub-catchment. Hydro-meteorological data collected from the National Meteorological Agency and Ministry of Water Resource, Irrigation and Electricity were used for model calibration and validation. SCS-CN, SCS-UH, Muskingum and monthly constant method were used for precipitation loss modeling, transform modeling, flood routing and base flow modeling respectively. Nash Sutcliff Efficiency and coefficient of determination have been selected for model performance evaluation. The model had shown good performance both during calibration and validation with (NSE = 0.855, R2= 0.867) for calibration and (NSE = 0.739, R2 = 0.863) for validation respectively. PBIAS for calibration and validation were checked and they were within the acceptable range with a value of 4.59% and 5.67% respectively. By the successful accomplishing of calibration and validation, the peak flood from the model (573.7m3/s) was compared with direct observed flow (546.4m3/s) and model provided nearly the same result with the direct observed flow.